2021
DOI: 10.1016/j.amjmed.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 Tachycardia Syndrome: A Distinct Phenotype of Post-Acute COVID-19 Syndrome

Abstract: In this paper we highlight the presence of tachycardia in Post-acute Covid-19 Syndrome by introducing a new label for this phenomenon: Post-covid-19 tachycardia syndrome and argue that this constitutes a phenotype or sub-syndrome in PACS. We also discuss epidemiology, putative mechanisms, treatment options and future research directions in this novel clinical syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(131 citation statements)
references
References 28 publications
0
94
0
11
Order By: Relevance
“…It should be emphasized that POTS is a rare medical condition, and the onset of tachycardia following SARS-CoV-2 or any other viral infection can be more frequently explained as a physiological response of a perfectly intact autonomic nervous system. It has been recently suggested that post-COVID-19 tachycardia syndrome would represent a distinct disease entity, different from classical POTS [48].…”
Section: Covid-19 Infection and Dysautonomiamentioning
confidence: 99%
“…It should be emphasized that POTS is a rare medical condition, and the onset of tachycardia following SARS-CoV-2 or any other viral infection can be more frequently explained as a physiological response of a perfectly intact autonomic nervous system. It has been recently suggested that post-COVID-19 tachycardia syndrome would represent a distinct disease entity, different from classical POTS [48].…”
Section: Covid-19 Infection and Dysautonomiamentioning
confidence: 99%
“…Many patients describe a postviral onset, [29][30][31][32] and 15%-20% of patients with POTS report a history of an autoimmune disorder such as Hashimoto thyroiditis, rheumatoid arthritis or Sjögren syndrome. 4 Recently, numerous cases of POTS 33 and other forms of sinus tachycardia (e.g., inappropriate sinus tachycardia) 34 after a SARS-CoV-2 infection have been reported. Good data on the frequency of POTS among patients with long-term complications from COVID-19 ("long COVID syndrome") are lacking.…”
Section: What Is the Pathophysiology Of Pots?mentioning
confidence: 99%
“…Initial reports, currently confirmed, have highlighted the following residual effects of SARS-CoV-2 infection: fatigue, dyspnea, chest pain, cognitive impairment, arthralgia, and decline in quality of life (61). Symptomatic tachycardia, either presenting as postural orthostatic tachycardia syndrome or inappropriate sinus tachycardia, is also frequently reported in post-acute COVID-19 syndrome (62). All these symptoms may pose problems of differential diagnosis with symptoms originating from a primary cardiovascular problem.…”
Section: Post-acute Covid-19 Syndrome "(Long Covid)"mentioning
confidence: 99%